Business Strategies for Effective Entrepreneurship: A Panacea for Sustainable Development and Livelihood in the Family (International Journal of Management and Sustainability, 2015)
This paper examines Business Strategies for Effective Entrepreneurship as a panacea for Sustainable Development and Livelihood in the Family. A strategy can generally be seen as a visionary plan of action aimed at attaining specific objectives. The paper observes that due to poor economic conditions in Nigeria, most families are threatened by poverty. The paper is anchored on the Discovery Theory/Individual Opportunity Nexus which is in tune with the fact that successful entrepreneurs can make innovations through exploring the environment so as to exploit viable opportunities. It is the position of this paper that effective entrepreneurship will enhance sustainable development and family livelihood. The implication of this is that most disadvantageous and impoverished families will benefit through the contributions of entrepreneurship with particular reference to Family Businesses. The family business thrives effectively when there is a harmony of interest. It is not in doubt that the family is a major institution for carrying out essential production, consumption, reproductions and accumulation functions that are associated with the social and economic empowerment of individuals and societies, all of which leads to sustainable development, improved standard of living and livelihood. Sustainable development connotes the development that will remain intact for an indefinite period possibly forever. Sustainable livelihood which is similar to sustainable development in Singh’s view Singh (2014) is fortifying “access of both present and future generations to secure the necessities of life such as food, clothes, shelter, security, freedom, basic literacy and health care on a long run”. If effective business strategies are imbibed, Entrepreneurship and Family businesses will thrive. The end result will be sustainable development and improved standard of living at the grassroots.